Regulation of mRNA stability contributes to the function of innate lymphoid cells in various diseases - Deng, Yuanyu; Shi, Saiyu; Luo, Jie; Zhang, Yiwei; Dong, Hui; Wang, Xian; Zhou, Jian; Wei, Zhiyuan; Li, Jiahui; Xu, Chen; Xu, Shuai; Sun, Yi; et al. (Frontiers in Immunology, 2023)
Innate lymphoid cells (ILCs) are important subsets of innate immune cells that regulate mucosal immunity. ILCs include natural killer cells, innate lymphoid cells-1 (ILC1s), ILC2s, and ILC3s, which have extremely important roles in the immune system. In this review, we summarize the regulation of mRNA stability mediated through various factors in ILCs (e.g., cytokines, RNA-binding proteins, non-coding RNAs) and their roles in mediating functions in different ILC subsets. In addition, we discuss potential therapeutic targets for diseases such as chronic obstructive pulmonary disease, cancer, and pulmonary fibrosis by regulation of mRNA stability in ILCs, which may provide novel directions for future clinical research.